Presidential Address: Visions and Revisions: The View from the Presidents’ Offices of Ontario Universities Since the Second World War - Neatby, H. (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1988)
AbstractOntario universities have been transformed since the 1940s. University presidents have played a crucial role in shaping these changes. In the 1950s they defended the concept of the liberal arts college, partly because other options seemed too risky.In the 1960s the government provided the finances and the presidents, separately and jointly, responded to the diverse demands of governments, faculties, and students. By the 1970s, the institutions had adapted to expansion, to a shift in balance between teaching and research, and to an emerging provincial system without any major crises or characters. Since the 1970s the government's policy of financial constraint has dominated discussions, with related debates on accessibility and private sector research. The university presidents have not yet defined new goals which the government considers realistic.